2022
DOI: 10.52711/0974-360x.2022.00209
|View full text |Cite
|
Sign up to set email alerts
|

In silico Study of Natural inhibitors for Human papillomavirus-18 E6 protein

Abstract: Globally, the leading cause of death from cancer in women is infection with the human papillomavirus (HPV). This calls for imperative actions to explore anticancer drugs against this threatening viral infection, in which case, natural ingredients are presumed to be a promising source. Several studies show that plant-origin compounds such as allicin, apigenin, capsaicin, cyanidin, fisetin, genistein, laricitrin, naringenin, piperine, and syringetin have demonstrated therapeutic effects against several cancer ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…It has several functions anti thrombus, anti-atherosclerosis, anticoagulation, anti-inflammation, and antioxidant [32]. Another research demonstrates the application of chondroitin sulfate-chitosan nanoparticles in treating malaria as a transdermal medication release mechanism [33]. This study revealed that chondroitin sulfate could bind PfHT1 using the same route as control (ASN311 and GLN305) but also bind with different active sites using hydrogen and hydrophobic bonds.…”
Section: Discussionmentioning
confidence: 85%
“…It has several functions anti thrombus, anti-atherosclerosis, anticoagulation, anti-inflammation, and antioxidant [32]. Another research demonstrates the application of chondroitin sulfate-chitosan nanoparticles in treating malaria as a transdermal medication release mechanism [33]. This study revealed that chondroitin sulfate could bind PfHT1 using the same route as control (ASN311 and GLN305) but also bind with different active sites using hydrogen and hydrophobic bonds.…”
Section: Discussionmentioning
confidence: 85%
“…14,15 Three-dimensional visualization of the molecules from the docking results was conducted by PyMol v2.5.2 (Schrodinger Inc., USA) with an academic license. 16,17 The molecule complexes from the docking results with the most negative binding-affinity value were then identified by using Discovery Studio Visualizer™ v16.1 (Dassault Systèmes SE, France) for the chemical interactions and bonds. The types of chemical bonds that can be identified from the docking results are hydrogen, hydrophobic, alkyl, electrostatic, and Van der Waals.…”
Section: Methodsmentioning
confidence: 99%
“…Sterilization of the target protein from water and contaminant ligands was carried out by Discovery Studio software to increase the optimization of binding energy. 20,24,25 Molecular docking and dynamic simulation…”
Section: Bioactivity and Drug Likeness Predictionmentioning
confidence: 99%